2005
DOI: 10.1073/pnas.0507479102
|View full text |Cite
|
Sign up to set email alerts
|

The DNA replication factor MCM5 is essential for Stat1-mediated transcriptional activation

Abstract: The eukaryotic minichromosome maintenance (MCM) family of proteins (MCM2-MCM7) is evolutionarily conserved from yeast to human. These proteins are essential for DNA replication. The signal transducer and activator of transcription proteins are critical for the signal transduction of a multitude of cytokines and growth factors leading to the regulation of gene expression. We previously identified a strong interaction between Stat1 and MCM5. However, the physiological significance of this interaction was not cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 39 publications
6
61
0
Order By: Relevance
“…The poor definition of mammalian origins of replication has made difficult to quantify with precision the amount of chromatin-bound MCM complexes relative to the number of origins. In any case, there must be a large excess of MCM relative to the number of replication forks, because the majority of chromatin-associated MCM complexes do not localize with sites of DNA synthesis (21 (22), and Mcm7 interacts with Rad17 and ATRIP and is likely required for activation of the DDR (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…The poor definition of mammalian origins of replication has made difficult to quantify with precision the amount of chromatin-bound MCM complexes relative to the number of origins. In any case, there must be a large excess of MCM relative to the number of replication forks, because the majority of chromatin-associated MCM complexes do not localize with sites of DNA synthesis (21 (22), and Mcm7 interacts with Rad17 and ATRIP and is likely required for activation of the DDR (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this large pool of MCM proteins is required, because even a partial reduction in MCM level that does not greatly affect DNA replication leads to increased recombination events, chromosome loss and checkpoint sensitivity (Bell and Dutta, 2002;Liang et al, 1999). The excess level of MCM proteins along with broad binding on chromatin has been termed the 'MCM paradox' (Forsburg, 2004;Hyrien et al, 2003;Laskey and Madine, 2003) and further studies have shown that MCM proteins have multiple functions outside of DNA replication, including transcriptional activation and repression, chromatin remodeling, meiotic recombination, chromatin cohesion, and checkpoint responses (Agarwal et al, 2007;Forsburg, 2004;Gauthier et al, 2002;Snyder et al, 2005;Sterner et al, 1998). It is significant that, in addition to the localization of MCM5 on centrosomes that is reported here, localization of both Orc2 and geminin has also been reported on centrosomes (Prasanth et al, 2004b;Stuermer et al, 2007;Tachibana et al, 2005).…”
Section: Journal Of Cell Science 121 (19)mentioning
confidence: 99%
“…However, these coactivators are not specific to STAT3, but are also implicated in the functions of other STAT family members as well as in oncoproteins (such as Myb, Jun, and Fos), transforming viral proteins (such as E1A, E6, and large T antigen) and tumor-suppressor proteins (such as p53, E2F, Rb, Smads, RUNX, and BRCA1) (Shuai, 2000;Litterst and Pfitzner, 2002;Iyer et al, 2004). Recently, MCM5 and CoaSt6 have been suggested as specific coactivators of STAT1 and STAT6, respectively, although their in vivo relevance needs to be determined (Snyder et al, 2005;Goenka and Boothby, 2006). These findings raise the possibility of the existence of an additional coactivator that binds specifically to STAT3 and modulates its transcriptional activity.…”
Section: Introductionmentioning
confidence: 99%